The Influence of Social Media Marketing Through TikTok with Brand Awareness and Brand Attitude as Mediating Variables on Purchase Intention on Jiniso Brand - Devisafira Jelita Putri; Rusdi Hidayat Nugroho (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Innovations in technology have far-reaching effects on many parts of society, including advertising and public relations. To reach customers and promote their wares, more and more businesses are relying on online media like social networking. Advertising on social media, particularly on TikTok, is efficient due to the platform's massive user base. With 127.5 million users in Indonesia as of April 2024, TikTok is gaining popularity for increasing brand recognition and driving purchasing desire. The primary objective of this research is to identify the elements that local fashion brand consumers consider most important when making a purchasing decision. One hundred and seventy people from Surabaya's TikTok community who have seen Jiniso videos filled out surveys for this quantitative investigation. In this work, PLS-SEM is used to analyze the data. The research found that there is a substantial relationship between purchase intention and social media marketing, brand awareness, and brand attitude. There is a strong mediation effect of brand attitude and brand awareness on the relationship between social media marketing and intent to buy. According to this research, social media marketing on TikTok that is both entertaining and educational may increase customers' interest in buying the advertised product.